Development and Results from Application of PCM-Based Storage Tanks in a Solar Thermal Comfort System of an Institutional Building—A Case Study - F. Javier Batlles; Bartosz Gil; Svetlana Ushak; Jacek Kasperski; Marcos Luján; Diana Maldonado; Magdalena Nemś; Artur Nemś; Antonio M. Puertas; Manuel S. Romero-Cano; Sabina Rosiek; Mario Grageda (Energies, 2020)
An important element of a solar installation is the storage tank. When properly selected and operated, it can bring numerous benefits. The presented research relates to a project that is implemented at the Solar Energy Research Center of the University of Almeria in Spain. In order to improve the operation of the solar cooling and heating system of the Center, it was upgraded with two newly designed storage tanks filled with phase change materials (PCM). As a result of design works, commercial material S10 was selected for the accumulation of cold, and S46 for the accumulation of heat, in an amount of 85% and 15%, respectively. The article presents in detail the process of selecting the PCM material, designing the installation, experimental research, and exergy analysis. Individual tasks were carried out by research groups cooperating under the PCMSOL EUROPEAN PROJECT. Results of tests conducted on the constructed installation indicate that daily energy saving when using a solar chiller with PCM tanks amounts to 40% during the cooling season.